Lectin histochemical aspects of the ovarian lamellae epithelium of Genypterus blacodes (Schneider, 1801) - Díaz, Alcira Ofelia (2012)
The composition and distribution of the glycoconjugates (GCs) secreted by the epithelium of ovarian lamellae with reference to the reproductive biology of Genypterus blacodes (Schneider, 1801) through lectin hi stochemistry is here discussed. In this species, the epithelial cells that line the ovarian c avity presented sharp morphological variations along the reproductive cycle related to the mucus secretion that accompanies oocyte ma turation. During sp awning season, residues of mannose and N-acetylglucosamine were detected in the glycocalyx of those cells using lectinhistochemistry. N-acetylgalactosamine and fucose were also observed in the same zone. The greatest variations in the lectinhistochemical pattern were found in the apical cytoplasm composition in comparison to the basal zone of the cells. The results of the present study were discussed by comparing their possible functional implications.